Reducing embryonic mtDNA copy number alters epigenetic profile of key hepatic lipolytic genes and causes abnormal lipid accumulation in adult mice. (30th July 2021) - Wang, Yakun; Wang, Xuan; Long, Qiaoming; Liu, Yuanwu; Yin, Tao; Sirota, Inna; Ren, Fazheng; Gu, Zhenglong; Luo, Junjie
Abstract : Adverse fetal environment, in particular a shortage or excess of nutrients, is associated with increased risks of metabolic diseases later in life. However, the molecular mechanisms underlying this developmental origin of adult diseases remain unclear. Here, we directly tested the role of mitochondrial stress in mediating fetal programming in mice by enzymatically depleting mtDNA in zygotes. mtDNA‐targeted plasmid microinjection is used to reduce embryonic mtDNA copy number directly, followed by embryo transfer. Mice with reduced zygote mtDNA copy number were born morphologically normal and showed no accelerated body weight gain. However, at 5 months of age these mice showed markedly increased hepatic lipidosis and became glucose‐intolerant. Hepatic mRNA and protein expressions of peroxisome proliferator‐activated receptor α ( Pparα ), a key transcriptional regulator of lipid metabolism, were significantly decreased as a result of increased DNA methylation in its proximal regulatory region. These results indicate that perturbation of mitochondrial function around the periconceptional period causes hypermethylation and thus suppressed expression of PPARα in fetal liver, leading to impaired hepatic lipid metabolism. Our findings provide the first direct evidence that mitochondrial stress mediates epigenetic changes associated with fetal programming of adult diseases in a mammalian system. Abstract : By enzymatically depleting mtDNA in zygotes, we can directly test the hypothesis that mitochondrial stress mediates fetal programming of metabolic disease. Reduction of zygote mitochondrial copy number causes increased hepatic lipid deposit, impaired insulin signaling, and elevated glucose intolerance. Perturbation of mitochondrial function around the periconceptional stage causes hypermethylation and thus suppressed expression of PPARα in adult liver, leading to impaired hepatic lipid metabolism.